Respuesta :
ANSWER
[tex]w = (x - 8)[/tex]
EXPLANATION
The given rectangle has area,
[tex]A = {x}^{2} - x - 72 \: {m}^{2} [/tex]
It was given to us that, the length of the rectangle is l=(x+8)
To find the width, we need to factor, the expression for the area.
We split the middle term to get,
[tex]A = {x}^{2} - 9x + 8x- 72 [/tex]
We now factor by grouping;
[tex]A = x(x - 9) + 8(x- 9)[/tex]
[tex]A = (x + 8)(x - 9)[/tex]
We know that area of a rectangle is
[tex]A = l \times w[/tex]
Hence the width of the rectangle is,
[tex]w = (x - 8)[/tex]
[tex]w = (x - 8)[/tex]
EXPLANATION
The given rectangle has area,
[tex]A = {x}^{2} - x - 72 \: {m}^{2} [/tex]
It was given to us that, the length of the rectangle is l=(x+8)
To find the width, we need to factor, the expression for the area.
We split the middle term to get,
[tex]A = {x}^{2} - 9x + 8x- 72 [/tex]
We now factor by grouping;
[tex]A = x(x - 9) + 8(x- 9)[/tex]
[tex]A = (x + 8)(x - 9)[/tex]
We know that area of a rectangle is
[tex]A = l \times w[/tex]
Hence the width of the rectangle is,
[tex]w = (x - 8)[/tex]
Hello!
The answer is:
The expression that represents the width of the rectangle is:
[tex]width=x-9[/tex]
Why?
We know that the area of a rectangle is equal to:
[tex]A=length*width[/tex]
We are given the function that represents the area of the rectangle and one of its sides, the length is equal to (x+8)
So, rewriting we have:
[tex]x^{2}-x-72 =(x+8)*width[/tex]
The coefficients of the variables of the given function are:
[tex]x^{2}=1\\-x=-1[/tex]
Now, to find the width, we need to find two numbers which its product gives as result "-72" and its addition gives as result the coefficient of the linear term of the function (x), its "-1".
Then,
We know that,
[tex](-9)*(8)=-72\\-9+8=-1[/tex]
So, the factors of the given function are:
[tex]x^{2}-x-72 =(x+8)*(x-9)[/tex]
Since, we already know that the length corresponds to "x+8", we know that the width corresponds to "x-9".
Proving that the factors are right,
Applying the distributive property, we have:
[tex](x+8)(x-9)=x^{2}-9x+8x-72=x^{2}-x-72[/tex]
Hence, the equation is satisfied and we can conclude that:
[tex]length=x+8\\width=x-9[/tex]
Have a nice day!